Bowel Lymphoma Causing Multiple Intussusceptions In Adult- Case Report and Review of Literature - Devi, Gita; MD; Singh, Lokesh; MD; Debi, Uma; MD; Sandhu, M S; MD (Archives of Clinical and Medical Case Reports, 2020)
Intussusception in adults is rarer than children and treatment in most cases in adults is surgical. Multiple Intussusceptions in our case with subacute intestinal obstruction and presence of abdominal lymphadenopathy with diffuse bowel wall thickening warrants non-surgical treatment. Presence of multiple intussusceptions is rare findings. We present a case of female aged 35 years presented with palpable abdominal lump associated with loss of weight and appetite. CECT abdomen showed abdominal lymphadenopathy and multisegmental small bowel thickening maximum upto 1.5 cm. Some segments of bowel also show aneurysmal dilatation associated with asymmetrical mural thickening. Telescoping of proximal bowel segment into adjacent distal bowel is seen in at least two places in ascending colon region (colocolic intussusceptions) and another in ileal loops (ileo-ileal). FNAC from the lymph nodes revealed non hodgkins lymphoma.